The Gig Economy and Young Graduates' Career Preferences: Between Freelancing and the Entrepreneurial Mindset - Perdana, Yoga; Syahrul, Alfattory Rheza; Sudono, Agus; Kurnia, Dede; Susanto, Eko (Integrasi Sains Media, 2025)
The expansion of the gig economy has introduced freelancing as a compelling career path for university graduates seeking autonomy, flexibility, and value-aligned work. However, the transition from traditional employment aspirations to freelance entrepreneurship is shaped by complex psychological and social mechanisms that remain underexplored. This study develops and tests a structural model of freelance entrepreneurial intention by integrating the Theory of Planned Behavior (TPB) with entrepreneurial identity and self-efficacy. Data were collected from 254 university graduates and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrate that attitude toward freelancing, subjective norms, and perceived behavioral control significantly influence the development of entrepreneurial identity. Entrepreneurial identity, in turn, strongly predicts the intention to pursue freelance work. While perceived behavioral control also directly affects intention, self-efficacy shows limited influence, suggesting that role internalization and social validation are more critical than confidence alone. Interestingly, subjective norms affect intention indirectly through identity rather than directly. This study contributes to entrepreneurship research by highlighting identity as a key mediating mechanism within non-traditional entrepreneurial pathways. The findings have practical implications for universities, policy-makers, and platform providers aiming to support sustainable freelance careers. Interventions emphasizing identity development—alongside skills and opportunity access—may better equip graduates to navigate the uncertainties of gig-based self-employment.